[D-Ala2, D-Leu5] Enkephalin Attenuates Hepatic Ischemia–Reperfusion Injury in Cirrhotic Rats - Liu, Jueying; Wang, Yuan; Pan, Qianling; Chen, Xueqing; Qu, Yifeng; Zhu, Hao; Zheng, Li; Fan, Yinghui (Frontiers in Surgery, 2022)
Background & Aims: Hepatic ischemia-reperfusion injury (IRI) is a common phenomenon after liver transplantation and liver tumor surgery. It can cause the liver dysfunction and recovery failed after liver surgery, even leading to acute liver failure. Our aims are to investigate the protective effect and related potential mechanism of [D-Ala2, D-Leu5] enkephalin (DADLE) treatment on hepatic IRI in rats’ cirrhotic livers. Methods: The models of liver cirrhosis and hepatic IRI were established with male Sprague-Dawley rats. DADLE at a dose series of 0.5, 1 or 5mg·kg-1 was injected intravenously to rats 10min prior hepatic ischemia and followed with 6h reperfusion. The serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), histological changes and liver cell apoptosis were used to assess liver IRI. Similar maneuvers were repeated using the optimal dose of DADLE and DOR antagonist natrindole hydrochloride (NTD). Serum ALT and AST levels, histological staining, hepatic apoptosis, and serum levels of tumor necrosis factor alpha (TNF-α) and interleukin 1β (IL-1β) were measured. Expression of protein kinase B (Akt) and its downstream proteins were evaluated by Quantitative real-time polymerase chain action (qRT-PCR) and Western blotting. Results: DADLE treatment at a dose of 5mg·mg-1 could reduce ALT and AST levels, hepatic apoptosis, inflammation, and preserve liver structure. These changes could be inhibited by NTD 10min prior DADLE injection. DADLE could elevate the expression of Akt and its downstream proteins and mRNA levels. Conclusion: DADLE treatment at a dose of 5mg·kg-1 injected intravenously 10min prior hepatic ischemia could relieve rats’ hepatic IRI through activating DOR in cirrhotic livers. The effects of DADLE could be offset by NTD. The potential molecular mechanism seems to be involved in phosphatidylinositol-3-kinase (PI3K)/Akt pathway.